Household Waste Communication Campaign in the Family Planning Village in Medan City - Lusiana Andriani Lubis; Syafruddin Pohan (Ikatan Sarjana Komunikasi Indonesia, 2021)
A research phenomenon is a model of communication carried out by district government officials to create public awareness about household waste. The aim of this research is to analyze the model of communication carried out by district government officials to make people aware of how to deal with household waste. This research uses the interpretive qualitative method, in which data are selected by purposive sampling. Data collection techniques are Focus Group Discussion and observation. The results of this research show that through face-to-face communication and group communication district government officials, ranging from the head of the environment office, family planning cadres and family welfare movement (PKK) activator team, community leaders to the village head, had tried to perform their duties properly in making residents in two areas of family planning (KB) village aware about the impact of household waste. Persuasive communication is the model of communication where the source actively seeks to influence the recipient who is in a passive position. Due to differences in perceptions, the process of exchanging messages during the campaign was one-way, namely from the source to the recipient. The model of communication which is developed in the activity is a command system in which district government officials give a command to the residents of the family planning village where the participation of the people especially those who rent houses in the management of household waste is low.